Effects of growth retardant (CCC) and growth promoter (GA) on morphology and productivity of bean (Phaseolus vulgaris L. cv. Carioca) - Castro, Paulo R. C.; Enok, Haiko (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
In this paper the autors tested the effects of (2 - chloroethyl) trimethylammonium chloride (CCC) and gibberellic acid (GA) on the cultivar Carioca of bean, in three different concentrations (500, 2000, and 4000 ppm) of CCC and one concentration of GA (50 ppm). Treatment with CCC 500 ppm + GA 50 ppm increased the height of bean plant and CCC 4000 ppm + GA 50 ppm reduced the height of Phaseolus vulgaris. Application of CCC 500 ppm + GA 50 ppm or CCC 2000 ppm + GA 50 ppm increased the leaf number of bean plant. CCC 500 ppm + GA 50 ppm promoted a increase in the internode length and CCC 4000 ppm + GA 50 ppm reduced the length of internodcs. Application of CCC 500 ppm + GA 50 ppm or CCC 2000 ppm + GA 50 ppm increased the leaf length 5 days after the treatment. CCC 500 ppm + GA 50 ppm promoted higher flowering in relation to the check..